Results of surgical alloplasty for bone defects of various locations due to distal humerus fractures - Aleksey P. Davydov; Andrej G. Chibrikov; Vladimir Yu. Ulyanov; Igor A. Norkin (Geniĭ ortopedii = Genij ortopedii, 2025)
Introduction Currently, up to 30 % of cases after surgical treatment in distal humerus fractures result in permanent disability. It is important to improve the surgical techniques to ensure the restoration of the anatomical integrity of this department. The aim of the work was to perform a comparative analysis of the results of surgical plasty with donor block and cubic cadaver allografts for bone defects of various locations in the distal humerus fractures based on an assessment of bone density and vascularization of the grafted area. Materials and methods The study involved 56 patients with distal humerus fractures, divided into three groups based on the defect location and two subgroups depending on the method of surgical plastic surgery. A comparative analysis of treatment outcomes was conducted based on the values of the vascularization index of the defect zone obtained by ultrasound study, as well as the Hounsfield index values obtained by computed tomography of the damaged segment. The allograft area was assessed in three zones of interest, the central, marginal and native bone structures. Results The use of a block allograft provided increase in the values of the Hounsfield index 3 months after surgery in the central graft zone with a defect in the medial column to a value of 190HU (p = 0.01),with a lateral defect to 185HU (p = 0.01), with a central defect to 170HU (p = 0.03); increased the values of the Hounsfield index in the marginal zone 3 months after surgery, the graft area with a medial defect was 210HU (p = 0.01), a lateral defect was 200 HU (p = 0.01), and a central defect was 185 HU (p = 0.02). It provided the increase in the values of the vascularization index of the graft zone with a defect in the medial column by 1.2 times (p = 0.01), in the lateral column by 1.15 times (p = 0.01), in the central zone by 1.18 times (p = 0.02). Discussion The results of the study indicate that the use of a block allograft increases the density of bone tissue in the marginal and central zones of defect grafting area 3 months after surgery, more expressed if it is localized in the medial and lateral columns, and increases the intensity of blood flow in the defect grafting area 2 months after surgery. Conclusion Comparison of the results of plastic surgery for post-traumatic bone defects in comminuted fractures of the distal humerus showed the advantage of using native block allograft in defects of the lateral and medial columns due to the optimization of osteointegration processes in the defect zone in the mediumterm postoperative period.